Knock-Down of Histidyl-tRNA Synthetase Causes Cell Cycle Arrest and Apoptosis of Neuronal Progenitor Cells in vivo - Waldron, Ashley; Wilcox, Claire; Francklyn, Christopher; Ebert, Alicia (Frontiers in Cell and Developmental Biology, 2019)
Histidyl-tRNA Synthetase (HARS) is a member of the aminoacyl-tRNA synthetase family, which attach amino acids to their associated tRNA molecules. This reaction is a crucial step in protein synthesis that must be carried out in every cell of an organism. However, a number of tissue-specific, human genetic disorders have been associated with mutations in the genes for aminoacyl-tRNA synthetases, including HARS. These associations indicate that, while we know a great deal about the molecular and biochemical properties of this enzyme, we still do not fully understand how these proteins function in the context of an entire organism. To this end, we set out to knock-down HARS expression in the zebrafish and characterize the developmental consequences. Through our work we show that some tissues, particularly the nervous system, are more sensitive to HARS loss than others and we reveal a link between HARS and the proliferation and survival of neuronal progenitors during development.